Restructuring and employment in the EU. The impact of globalisation - Storrie, Donald; Ward, Terry (Luxembourg, 2007)
"This report provides some perspectives on the effects of trade liberalisation on the European labour market. For its analysis, it draws on data from the European Restructuring Monitor (ERM), the only EU-wide monitoring instrument available. The 2007 ERM report identifies some of the recent and emerging trends in the current phase of globalisation and provides suggestions on how policy should be re-oriented to address these new circumstances."